Depressive symptoms and associated factors among travestis and transsexuals: a cross-sectional study - Glauber Weder dos Santos Silva; Karina Cardoso Meira; Eder Samuel Oliveira Dantas; Sávio Marcelino Gomes; Iago Matheus Bezerra Pedrosa; Francisco Arnoldo Nunes de Miranda (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to estimate the prevalence of depressive levels and their associated factors among transvestite and transsexual individuals. Methods: this cross-sectional study involved 58 participants assisted by non-governmental organizations. The Beck Depression Inventory was utilized to assess levels of depression, complemented by a sociodemographic questionnaire and a questionnaire on experiences of violence. Data were analyzed using descriptive statistics and Poisson regression with robust variance. Results: a prevalence of 27.6% (95% CI = 11.50-39.10) for moderate to severe levels of depression was observed. This prevalence was associated with being unmarried (PR = 1.19; 95% CI = 1.10-1.28) and experiencing violence in healthcare services (PR = 2.30; 95% CI = 1.10-4.81). Conclusions: the absence of a partner and experiences of violence in healthcare settings negatively impacted mental health, leading to an increased prevalence of depressive symptoms among transvestite and transsexual individuals. Advocating for transgender rights and providing ongoing education in health care for professionals are critical strategies in promoting the mental health of this population.